Long-wavelength transition radiation by relativistic electrons in a pre-wave zone - Dobrovolsky, S.N.; Shul’ga, N.F. (Вопросы атомной науки и техники, 2001)
The spectral-angular density of electromagnetic energy flux through the small detector in the "pre-wave zone" caused by relativistic electron in "forward" direction in the case of normal electron transition through a thin metallic transverse-bounded target is investigated. We show that detected intensity can be very differ from the spectral-angular density of radiation as well it is measured in the "wave zone" as it is measured in "pre-wave zone" by infinite detector. This distortion is depended from the detector placing in the "pre-wave zone" and from the ratio between transversal size of target and effective transversal diameter of radiation formation region.